REGULASI DIRI PADA MAHASISWA REGULER DAN MAHASISWA BEKERJA DI TAHUN PERTAMA KULIAH - Grahani, Firsty Oktaria; Agustin, Ardianti; Lailiyah, Alfu Fitrotul; Rahardjo, Natasha Valentina (Universitas Muhammadiyah Gresik, 2024)
Background: In the face of various academic, social and personal demands, self-regulation is an important factor that can help students organize their time, manage stress, and achieve their goals. Both regular and working students arefaced with a more independent or autonomous environment. Self-regulation infirst-year college students is important because this period is the initialfoundation that will shape learning habits and performance in the following year. Objective: The purpose of this study was to determine the dynamics of self-regulation of regular students and working students in the first year of college and the factors that influence self-regulation. Method: This research is aphenomenological qualitative research with semi-structured interview method.The analysis technique is Interpretative Phenomenological Analysis (IPA).Result: The results found that the choice to continue further study was influencedby internal and external factors from each student concerned. There are severalaspects of self-regulation that are quite influential, namely time management,goal orientation and motivation regulation, which of course have differentcharacteristics between regular and working students. Conclusion: Theimportance of self-regulation for students in order to achieve academic success,especially for regular students. Meanwhile, students work to maintain a balancebetween academic and career success.